Permodelan GARCH pada IHSG dan Indeks LQ45 - R Adisetiawan; Nuraini Nuraini; Hana Tamara Putri; Ahmadi Ahmadi (J-MAS (Jurnal Manajemen dan Sains), 2021)
ARCH and GARCH models are widely used to describe the form of volatility of a heteroskedastic time series data. Volatility is a measure of how far a stock price or stock price index moves in a given period. The LQ45 Index is an index that measures the performance of stocks of various companies that are operationally for the types of stocks that have high liquidity. The stock price index used is the LQ45 index for the period 2016.09-2021.09. The return of the stock price index is modeled in the best form of GARCH univariate. Research shows that the best GARCH univariate model is EGARCH (3,3).